The Influence of Career Development and Work Environment on The Turnover Intention of Employee Millennial Who Lives in RW 10, Depok Village, Depok City - Soedira, Verrell Nathaniel; Husniati, Renny; Rialmi, Zackaria (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
ABSTRACT This research is a quantitative study that aims to determine whether there is an influence of career development and work environment on the desire of millennial generation employees who live in RW 10, Pancoran Mas District, Depok Village, Depok City to leave the company where they are currently working. This study used 75 respondents from 108 residents aged 21-40 who lives in RW 10, Pancoran Mas District, Depok City. The hypothesis in this study is to determine the effect partially and simultaneously so that the test uses the T test and F test with the help of the SPSS version 25 statistical program. The results of the test are (1) There is a negative and significant effect of giving career development for millennial generation RW 10 employees on the desire to leaving the company, (2) there is a positive and significant influence on the work environment of RW 10 millennial employees on the desire to leave the company, (3) there is a significant influence on career development and the work environment affecting the desire of millennial generation employees to leave the company. Keywords : Career Development, Work Environment and Turnover Intention